Diagnostic Delay in Rheumatoid Arthritis: A Qualitative Study of Symptom Interpretation Before the First Visit to the Doctor. (5th June 2015) - Mølbæk, Karen; Hørslev‐Petersen, Kim; Primdahl, Jette
Abstract: Background: To prevent joint damage among patients with rheumatoid arthritis (RA), there is a need to minimize delays from the onset of symptoms until the initiation of appropriate therapy. The present study explored the factors that have an impact on the time it takes for Danish patients with RA to approach their general practitioner (GP) with joint pain, and also how GPs respond to patients' complaints. Methods: The study was based on qualitative data collected using 11 semi‐structured individual interviews. Results: When symptoms were obvious to patients, there was a shorter delay between symptom onset and contacting their GP. In cases where symptoms gradually worsened or were difficult to interpret, there was a longer delay. Participants with a high degree of body awareness appeared to be good at detecting when something was not normal, and they responded quickly to their symptoms. For those who regarded the doctor as a resource to which they were entitled and who were not worried about getting a diagnosis there was a shorter delay. Diffuse symptoms seemed to confuse GPs and can contribute to physician delay in the investigation process. Similarly, the presence of other diseases can result in a prolonged period before referral to a rheumatologist. Conclusions: The nature and severity of symptoms are the deciding factors in their interpretation, by both the GP and the patient. Both the patient's disease recognition and his/her subsequent interaction with the doctor is influenced by the patient's body awareness and general attitude towards going to the doctor. The results showed that the greater the patient's body awareness, the better the disease recognition, the fewer barriers to contacting the GP and the shorter the delay in doing so. Copyright © 2015 John Wiley & Sons, Ltd.